Comparison of The Effectiveness of Use Antiseptic Povidone Iodine 10% And Octenidine Hydrochloride 0.1% in The Action of Neuroaxial Blocks in Patients Who Will Surgery in Haji Adam Malik General Hospital Medan - Bejo Utomo Handayani; Luwih Bisono; Dadik Wahyu Wijaya; Rina Amelia (JAI (Jurnal Anestesiologi Indonesia))
Background: Antiseptics or germicides are chemical compounds used to kill or inhibit the growth of microorganisms on living tissue such as the surface of the skin and mucous membranes.